Hubungan Penggunaan Air Conditioner (AC) di Ruang Kelas Terhadap Kejadian Sindrom Mata Kering Pada Pelajar SMA Negeri Bandar Lampung - Amalia Widya Larasati; Rani Himayani (Majority, 2020)
Using Air Conditioner (AC) in daily life have become a habit. AC is used to give a cozy condition but in the other side, AC causes low humidity and causing dry eye syndrome. The purpose of this research was to know the correlation between using AC in classroom and dry eye syndrome. The design of this study was analytic observational by using cross-sectional design. Subject of the research was XII grade students of Senior High School (SHS) 9 and 14 Bandar Lampung. There were 60 students from SHS 9 which using AC in classroom, and 60 students from SHS 14 which not using AC in classroom. Samples were selected by consecutive sampling and evaluated using schirmer test. Then, samples divided into normal and dry eye syndrome. Data analysis was using Chi Square test. The percentage of students who use AC in classroom and suffering dry eye were 61,7%. Meanwhile, students who don’t use AC in classroom and suffering dry eye were 20% (p=0,001). There was significant correlation between using AC in classroom and the incident of dry eye syndrome in Senior High School student at Bandar Lampung.